As razões de um estado rendido à arbitragem tributária - Ribeiro, Ana Rita Vilela (2018)
The 21st century brought us a globalized world. This globalization reflects itself on social and economic dynamics, which adapt themselves to whatever happens at an astonishing rate. Furthermore, the quantity of these relations also increases, and thus, the number of conflicts. States must find solutions in order to guarantee celerity. Precisely for reasons of celerity and efficiency, States, at an increasing rate, started to change the way they look at Justice, acknowledging their flaws and lack of efficient response. It was this problem that led the Portuguese State to open their jurisdiction to Arbitration, as an Alternative Jurisdictional Mechanism for Private and Public litigation, with constitutional recognition. We must evaluate how the public legal relations reacted to this new reality, specially regarding the Tax sector, since Portugal was a pioneer on the introduction of a Tax Arbitration Regime. We studied the State’s goals regarding the creation of this Regime, analysing, seven years after the beginning of the implementation, if their purposes are being fulfilled. With that in mind, we propose four solutions to improve the Regime’s efficiency. Two of them in adjustments to the legal diploma, namely reopening the permission period to use the migration regime from judicial courts to arbitral courts, whose validity of only one year proved to be insufficient. We also propose the introduction of a system of judicial patronage regarding tax arbitration, to remove inequalities in the access to the system. Besides, we propose to broaden the Alternative Dispute Resolution in the tax sector, namely through Conciliation (in similar ways to the civil procedure code) and Mediation (a similar regime to the Tax Arbitration analysed).